Pengaruh Layanan Bimbingan Klasikal Terhadap Kepribadian Muslim Pada Siswa Kelas IX SMP Unismuh Makassar - Muh Hariandika; Ahmad Nashir; Pertiwi Nurani (Jurnal Pendidikan Sosial Dan Konseling, 2026)
This study aims to determine the effect of classical guidance services on the Muslim personality of ninth-grade students at SMP Unismuh Makassar. The background of this research is the importance of forming a Muslim personality as a fundamental foundation in Islamic religious education, especially among adolescents who are experiencing a transitional period of development. The phenomena found indicate that there are still students who lack discipline in carrying out worship and show behavior that does not reflect Islamic values in daily life. This study uses a quantitative approach with saturated sampling technique, so that the entire population of 53 ninth-grade students was used as the research sample. Data collection techniques were carried out through structured questionnaires and documentation, while data analysis used Pearson correlation test, simple linear regression test, and coefficient of determination. The results showed that classical guidance services had no significant effect on students' Muslim personality. The R Square value of 0.006 indicates that the contribution of classical guidance is only 0.6%, while the remaining 99.4% is influenced by other factors such as family environment, religious activities at school, daily associations, and students' internal factors. The correlation test shows a very low relationship with a value of r = 0.077, while the results of the simple linear regression test reinforce the finding that there is no significant influence between the two variables. Thus, although the implementation of classical guidance at SMP Unismuh Makassar takes place regularly and systematically as part of the guidance and counseling program, this service has not had a significant effect on the formation of students' Muslim personality. This study recommends the need to optimize the implementation of classical guidance through diversification of methods, strengthening Islamic material, and more intensive collaboration with school religious programs and parental involvement.